2014
DOI: 10.1177/0004867414533837
|View full text |Cite
|
Sign up to set email alerts
|

The impact of 5-HTTLPR on acute serotonin transporter blockade by escitalopram on emotion processing: Preliminary findings from a randomised, crossover fMRI study

Abstract: While preliminary, our findings comprise the first pharmacogenetic study demonstrating an effect of the 5-HTTLPR 'S' allele load on escitalopram-induced changes in amygdala activity during emotional processing, consistent with a 5-HTT expression dosage model. The present findings have implications for the impact of this polymorphism on antidepressant efficacy in patients with mood and anxiety disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 80 publications
2
19
0
Order By: Relevance
“…Our finding of non‐significant decreases in amygdala responses after citalopram treatment in S/Lg carriers is distinct from previous evidence showing decreased amygdala responses to SSRI treatment in unselected MDD patients (Sheline et al ., ; Fu et al ., ). However, a recent study showed increased activity in the amygdala to negative stimuli with 7 days of escitalopram (s‐isomer of citalopram) treatment in healthy volunteers carrying the 5‐HTTLPR‐S/Lg allele compared to the LL genotype (Outhred et al ., ). Taken together our findings with the earlier study results, it is possible that 5‐HTTLPR may modify the effect of SSRIs on amygdala responses to negative emotions.…”
Section: Discussionmentioning
confidence: 97%
“…Our finding of non‐significant decreases in amygdala responses after citalopram treatment in S/Lg carriers is distinct from previous evidence showing decreased amygdala responses to SSRI treatment in unselected MDD patients (Sheline et al ., ; Fu et al ., ). However, a recent study showed increased activity in the amygdala to negative stimuli with 7 days of escitalopram (s‐isomer of citalopram) treatment in healthy volunteers carrying the 5‐HTTLPR‐S/Lg allele compared to the LL genotype (Outhred et al ., ). Taken together our findings with the earlier study results, it is possible that 5‐HTTLPR may modify the effect of SSRIs on amygdala responses to negative emotions.…”
Section: Discussionmentioning
confidence: 97%
“…For example, the polymorphism 5-HTTLPR occurs in the gene SLC6A4 that codes for the serotonin transporter, and there is some evidence that carriers of the long (l ) allele are more likely to respond to SSRI treatment than carriers of the short (s) allele [93]. In a cohort of healthy female participants, those with more l alleles showed more of an increase in left amygdala response after a single dose of escitalopram when viewing positive or neutral pictures, and more of a decrease in left amygdala response when viewing negative pictures [94]. The effects of the polymorphism on response to escitalopram treatment may therefore be mediated through its effects on early neuropsychological changes.…”
Section: (A) Explaining Individual Differences In Treatment Responsementioning
confidence: 99%
“…All participants were tested under placebo (saccharin) and escitalopram (20 mg; per os) conditions using a randomized, doubleblind, placebo controlled cross-over design, with a washout period of one week (or five half-lives, t 1/2 ¼ 26.7 h; Sogaard et al, 2005), as described previously (Hanson et al, 2013;Kemp et al, 2014;Outhred et al, 2014aOuthred et al, , 2014b. The present study reports fMRI findings on the emotion regulation task we employed (an eventrelated design with reappraisal of negative images).…”
Section: Experimental and Emotion Regulation Task Designmentioning
confidence: 99%
“…The present study reports fMRI findings on the emotion regulation task we employed (an eventrelated design with reappraisal of negative images). Our previous papers (Outhred et al, 2014a(Outhred et al, , 2014b reported on fMRI findings from a basic emotion processing task (a blocked design viewing negative, positive, and neutral images). The emotion regulation task results have not been previously reported.…”
Section: Experimental and Emotion Regulation Task Designmentioning
confidence: 99%